2023
DOI: 10.3389/fpsyg.2023.1108333
|View full text |Cite
|
Sign up to set email alerts
|

Transformative experience and informed consent to psychedelic-assisted psychotherapy

Abstract: Just as psychedelic-assisted psychotherapy (PAP) represents a clinical innovation that may need to be accommodated with corresponding theoretical and methodological innovations, there is growing awareness that the tools, normative frameworks, and standard practices of our clinical ethics may also need to be adapted, renewed, or replaced to accommodate its unusual features. Drawing on L. A. Paul's work on “Transformative Experience,” I argue that the acute and long-term effects that are repeatedly reported foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 96 publications
0
12
0
Order By: Relevance
“…However, Jacobs argues that owing to the particular effects of psychedelics-namely, mystical and ego-dissolution experiences which can occur acutely after administration and longer-term shifts in identity and values-the typical standards for informed consent may not be feasible. 14 Issues of capacity and consent during the psychedelic experience have received less attention. Individuals using psychedelics often experience profound acute changes to their sensorium along with alterations in mood, detachment from the body, and distortions of their sense of self, time, and reality.…”
Section: Informed Consent In Papmentioning
confidence: 99%
“…However, Jacobs argues that owing to the particular effects of psychedelics-namely, mystical and ego-dissolution experiences which can occur acutely after administration and longer-term shifts in identity and values-the typical standards for informed consent may not be feasible. 14 Issues of capacity and consent during the psychedelic experience have received less attention. Individuals using psychedelics often experience profound acute changes to their sensorium along with alterations in mood, detachment from the body, and distortions of their sense of self, time, and reality.…”
Section: Informed Consent In Papmentioning
confidence: 99%
“…Chan, 2023). 9 For example, it has already been applied in religious studies (e.g., Blanchard & Paul, 2021;Chan, 2019;De Cruz, 2018), education studies (e.g., Paul & Quiggin, 2020;Yacek, 2020;Yacek & Gary, 2020), psychology (e.g., Brouwer & Carhart-Harris, 2021;Forstmann et al, 2020;Yudkin et al, 2022), medical ethics (e.g., Egerton & Capitelli-McMahon, 2023;Hofmann, 2023;Jacobs, 2023;Letheby & Mattu, 2022;McQueen, 2017;Peterson et al, 2022;Walsh, 2020), and other areas of philosophy besides decision theory (e.g., Akhlaghi, 2023;Aumann, 2022;Carel et al, 2016;Carel & Kidd, 2020). Since it is not possible to cover all of these topics, I will focus on work that applies the concept of transformative experiences to illness, medical treatment, and the ethical issues involved.…”
Section: Transformative Experiences Beyond the Decision-theoretical C...mentioning
confidence: 99%
“…Villiger, 2024aVilliger, , 2024b. Jacobs (2023) and Egerton and Capitelli-McMahon (2023) are skeptical. In contrast, Smith and Sisti (2021) argue that informed consent to psychedelic-assisted therapy is possible under an enhanced informed consent process.…”
Section: Transformative Experiences Beyond the Decision-theoretical C...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, obtaining meaningful informed consent to psychedelic treatment will be challenging, given the unique effects of the drugs—including what are often described as the ineffable elements of the psychedelic experience, such as ego dissolution . Although some commentators have suggested that informed consent to psychedelic treatment, in the usual sense of that term, is simply unattainable, a growing consensus has coalesced around the notion that with proper attention to content and presentation, clinicians will be able to obtain meaningful and valid consent from patients…”
mentioning
confidence: 99%